The Card Catalogue: Is it an Effective Retrieval Tool in Present Day Information Work? - Entsua-Mensah, Clement (Ghana Library Journal, 1989)
Access to document files has been greatly improved with the introduction of computers into libraries and documentation centres. Quite apart from the traditional author and title elements, entries are made using ISBD elements, Keywords from titles, abstracts or text from documents, conference or report numbers, etc. to facilitate information retrieval. This has led some people to question whether the card catalogue is effective as an efficient retrieval tool. The Paper looks at some of the issues raised in-sa-far as the multi-access facility provided by computer-based systems vis-a-vis the constraints imposed by the Card Catalogue.